Predisposing factors to hypertension among junior staff of University of Ibadan, Ibadan Oyo State, Nigeria (2016)
The study examined psychosocial and economic variables as predisposing factors to hypertension among junior staff of University of Ibadan, Ibadan, Oyo State, Nigeria. A descriptive survey research design was adopted for the study. The study sampled 1004 respondents using simple random sampling technique. Data were collected through questionnaire. The result of the study shows that psychological variables (F(2,1001)=44.715, p<0.05) as mil as social variables (F(3,1000)=26.506, p<0.05) were predisposing factors to hypertension among junior staff of University of Ibadan while economic factor was not. It was concluded that psychological and social variables were predisposing factors to hypertension in the study. It was recommended that management of educational institutions in the country should ensure good physical and emotional work environment so as to enhance health status of workers.